2021
DOI: 10.3390/jcm10040745
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Body Composition Are Associated with Metabolic Changes and the Risk of Metabolic Syndrome

Abstract: In a cohort of 190,599 participants from The National Health Insurance Service-National Health Screening (NHIS-HEALS) study, we investigated the association of changes in the predicted body composition and metabolic profiles with the risk of metabolic syndrome (MetS) in the general population, which was hitherto incompletely elucidated. At baseline and follow-up examinations, the body composition, including lean body mass (LBM), body fat mass (BFM), and appendicular skeletal mass (ASM), were estimated using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 46 publications
2
20
0
Order By: Relevance
“…However, the classification errors caused by prediction equations may be reduced as we estimated the changes in each variable of same person. In addition, according to the previous study using the same prediction equations, an increase in the relative LBM and ASM was associated with the lower risk of metabolic syndrome, whereas an increase in the relative BFM was associated with the greater risk of metabolic syndrome, 35 which is in line with our findings. Considering the metabolic syndrome is a well‐known major risk factor for CVD, our findings may be sufficiently reliable.…”
Section: Discussionsupporting
confidence: 92%
“…However, the classification errors caused by prediction equations may be reduced as we estimated the changes in each variable of same person. In addition, according to the previous study using the same prediction equations, an increase in the relative LBM and ASM was associated with the lower risk of metabolic syndrome, whereas an increase in the relative BFM was associated with the greater risk of metabolic syndrome, 35 which is in line with our findings. Considering the metabolic syndrome is a well‐known major risk factor for CVD, our findings may be sufficiently reliable.…”
Section: Discussionsupporting
confidence: 92%
“…We additionally found signi cant inverse associations between muscle mass increases and changes in the total cholesterol and triglyceride concentrations. While pediatric data is limited, large adult studies have shown similar associations [13]. Our data indicate that weight increases in the form of muscle mass in youth may have metabolic health bene ts in the youth and furthers the well-known bene ts of regular exercise and muscle building for the overall metabolic health of youth.…”
Section: Discussionsupporting
confidence: 63%
“…Indeed, research indicates that a 1‐MET increase in CRF correlates with a decrease in cardiovascular risk factors often comorbid with obesity (i.e., hypertension, metabolic syndrome) of up to 22% and a reduced risk of arrhythmias and heart failure in adults with obesity by at least 6% and 21%, respectively (87‐90). Equally, whereas increased muscle mass is positively linked with a greater resting metabolic rate (i.e., 1 kg of muscle gained equals an increase of ~21 kcal/kg) (81), which is significant for weight loss, improvements in lean mass have been shown to more considerably impact health outcomes by decreasing the risk of metabolic syndrome in WLO by up to 33% (91).…”
Section: Discussionmentioning
confidence: 99%